1998
DOI: 10.1063/1.477672
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization of a polymer on a surface

Abstract: We have studied the structure and free energy landscape of a semiflexible lattice polymer in the presence of the surface of a polymer crystal. At low temperatures coexistence of two-dimensional integer-folded crystals is observed. As the temperature is increased there is a transition from these crystalline configurations to a disordered coil adsorbed onto the surface. The polymer then gradually develops a three-dimensional character at higher temperatures. We compute the free energy as a function of increasing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 50 publications
0
49
0
Order By: Relevance
“…The possibility of a two-stem nucleus was first suggested by Point 24 and recently strong evidence for this nucleus has been obtained in a study of the free energy profiles along specific crystallization pathways. 37 This finding about the structure of the initial nucleus puts a significant dent into LH theory because its assumption about the nature of the initial nucleus, and the resulting free energy barrier, is crucial to the theory. However, this finding is rendered somewhat irrelevant because the above results also undermine a more fundamental tenet of the LH theory, namely, the assumption that the thickness of a layer is determined by the initial nucleus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The possibility of a two-stem nucleus was first suggested by Point 24 and recently strong evidence for this nucleus has been obtained in a study of the free energy profiles along specific crystallization pathways. 37 This finding about the structure of the initial nucleus puts a significant dent into LH theory because its assumption about the nature of the initial nucleus, and the resulting free energy barrier, is crucial to the theory. However, this finding is rendered somewhat irrelevant because the above results also undermine a more fundamental tenet of the LH theory, namely, the assumption that the thickness of a layer is determined by the initial nucleus.…”
Section: Resultsmentioning
confidence: 99%
“…Such a nucleus is energetically favoured because of the interactions between the two stems. As it avoids the large free energy barrier associated with a single-stem nucleus 37 there is now no advantage in the initial stems being shorter than the average in the layer ͓Fig. 4͑a͔͒.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This application generated data that was used to confirm the validity of particular growth models. [124][125][126] This is the first study where high growth rates can be observed with high spatial and temporal resolution (normally fast growth is measured with optical microscopy, which is inherently limited to low spatial resolution by the diffraction limit of light).…”
Section: Magnesium Chloride Crystallisationmentioning
confidence: 99%